MODERN ASPECTS OF THE USE OF MAGNETIC RESONANCE IMAGING IN THE DIAGNOSIS OF OVARIAN CANCER - Babayarov Akmal Saitkulovich (Scholar Express Journals, 2024)
At present, ovarian malignancies occupy the third place among gynecologic cancers, being the main cause of death among female reproductive diseases. Due to the lack of effective screening programs and asymptomatic course in the early stages, ovarian cancer is most often detected in disseminated stages, which reduces the effectiveness of primary treatment and worsens the prognosis. Therefore, timely diagnosis, implementation of screening and careful monitoring of ovarian cancer recurrences are becoming key tasks in oncology. This review reviews the experience of using magnetic resonance imaging (MRI) for the diagnosis of primary ovarian cancer and its recurrence, and analyzes the effectiveness of this method taking into account different approaches. Modern MRI capabilities provide extensive information about the characteristics of ovarian masses, the spread of primary cancer and its recurrence. However, a review of the literature revealed a lack of research on the diagnostic capabilities of various MRI techniques, including diffusionweighted images (DWI). This underscores the need for more extensive research in this area
Keywords: Magnetic Resonance Tomography; Ovarian Cancer; Ovarian Cancer Recurrence; Peritoneal Carcinomatosis